A Polynomial Representation and a Unique Code of a Simple Undirected Graph. (27th August 2013) - Ghosh, Shamik; Sen Gupta, Raibatak; Sen, M. K.
Abstract : We introduce a representation of simple undirected graphs in terms of polynomials and obtain a unique code for a simple undirected graph.